Effect of Multivoice Chorus on Interpersonal Communication Disorder - Huiling Lei (Occupational Therapy International)
Objective. As a type of music therapy, multipart chorus does not have high requirements for participants, and the basic level can be high or low. For college students, it is more likely to participate. Exploring the effect of multivoice chorus intervention on college students’ mental health can provide reference for school psychological correction work. This study uses multivoice chorus as a means, combined with certain group psychological counseling techniques, to try to explore a new model for improving the mental health of college students. Method. Fifty college students in prison were selected as subjects and randomly divided into the control group and experimental group. The multivoice chorus method was used to conduct an intervention test on the mental health of the college students in the experimental group, and the observation was carried out for 3 months. Before and after the intervention, the anxiety self-rating scale, the trust scale, the social avoidance and distress scale, the shyness scale, the UCLA loneliness scale, and the college student psychological test personality subtest were used for psychological testing and evaluation. Results/Discussion. College students can actively recognize and reflect on their own behavior, and objectively evaluate others. Through the cognition and management of emotions, college students can handle personal emotions well in interpersonal communication. In the later stage of multivoice chorus, they can help each other, establish a mutual assistance system, help each other, and discuss and learn interpersonal communication skills together, so that college students can learn good interpersonal communication experience and skills from others in various interactions, achieve self-help, and promote college students to work together. In the process of interfering with interpersonal communication disorder, simple psychological counseling has also improved the phenomenon of interpersonal communication disorder, but the experimental effect is far from the effect of the combination of music education and psychological counseling, and it is relatively unstable in the stability test. In the specific operation, in the purely psychological counseling process, college students with interpersonal barriers do not actively cooperate with the intervention, the operating atmosphere is relatively dull, and the teachers are time-consuming and labor-intensive during the psychological counseling process, but the results are minimal. The only effect is also worn out within a few weeks, and the stability is poor. It can be seen that music education has played a pivotal role as a medium in the intervention of interpersonal communication disorders, which can make the intervention process easier, more effective, and more stable.